Antibacterial magnetic compatible medical beta-type Zr-Nb-Cu alloy and preparation method thereof
By alloying Nb and Cu in β-type Zr-Nb-Cu alloy, the elastic modulus and magnetic susceptibility are reduced, the elastic modulus mismatch and MRI artifacts of β-type titanium alloy in surgical implantation are solved, and the elastic modulus mismatch and MRI artifacts of β-type titanium alloys are imposed on the surgical implantation of β-type titanium alloys. Its highly efficient antibacterial properties are suitable for clinical implantation and MRI detection, reducing the risk of bacterial infection.
Patent Information
- Application Number
- CN202411420030.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The existing β-type titanium alloy has the problem that the elastic modulus does not match the human bones in the field of surgical implantation, which leads to the 'stress shielding effect', and the artifacts are caused by high magnetic susceptibility in MRI detection, and lacks antibacterial function, which is prone to bacterial Infect.
Develop an antibacterial magnetically compatible β-type Zr-Nb-Cu alloy. By alloying Nb and Cu elements, the elastic modulus and magnetization of the alloy are reduced, while giving it efficient antibacterial properties. The alloying design of Nb and Cu is adopted. , the mass percentage of Nb is controlled is 18% to 24%, and the mass percentage of Cu is 4% to 10%, so as to form a fully stable β phase and solid-soluble Cu, and improve the mechanical properties and antibacterial ability of the alloy.
The alloy is achieved with low elastic modulus and low magnetic susceptibility, adapted to human skeleton and MRI detection, significantly improved the antibacterial rate against Staphylococcus aureus, reduced the risk of postoperative infection, and low cost, avoiding the dependence of precious metals. .
Smart Images

Figure CN119287215A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical metal materials, and in particular to an antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy and a preparation method thereof. Background Art
[0002] Biomedical metal materials, also known as surgical metal materials, usually have high mechanical strength and fatigue resistance, and are the most widely used load-bearing implant materials in clinical applications. Compared with conventional clinical implant materials such as medical stainless steel and cobalt-based alloys, titanium-based alloys have become the first choice for implant products such as artificial joints, dental implants, and spinal correction and fixation systems due to their lower elastic modulus, excellent biocompatibility, and corrosion resistance. However, with the development of medical technology and the continuous application of surgical implants in the clinical field, titanium-based materials represented by β-type titanium alloys still have obvious deficiencies in the field of surgical implants. One of them is that the elastic modulus of most β-type titanium alloys (70GPa~120GPa) is still not well matched with the elastic modulus of human bones (10GPa~30GPa), which can easily cause a "stress shielding effect" and is not conducive to bone healing and the long-term stability of implants; in addition, the magnetic susceptibility of titanium-based alloys is relatively high (3.5×10 -6 ~3.7×10 -6 cm 3 / g), magnetization will occur in the strong magnetic field of MRI (Magnetic resonance imaging), causing the implant to heat up, shift, and form an artifact area. Therefore, considering that most surgical operations need to be performed under MRI, it is urgent to design and develop a medical metal material with compatible magnetic susceptibility and elastic modulus in this field.
[0003] Bacterial infection caused by implanted devices is also an important problem that needs to be solved clinically. Most medical metal materials have no antibacterial function, and bacteria can easily adhere to the surface. Even if aseptic operation is strictly performed during surgery, the use of antibiotics after surgery still cannot reduce bacterial infection of the implant. In severe cases, it can lead to complications and eventually lead to implant failure. Therefore, medical materials with antibacterial function are particularly important for reducing postoperative infection and prolonging the life of implants. Adding an appropriate amount of metal element films such as Cu and Ag with strong antibacterial effects to the surface modification layer of medical metal materials is a direct measure to deal with bacterial infection of implanted metals. In addition, the overall antibacterial function can be obtained by alloying Cu or Ag elements in medical metals. For example, the antibacterial rate of copper-containing 316 / 317L stainless steel against Candida albicans, Staphylococcus aureus, and Escherichia coli is as high as 90%. Compared with Cu, Ag has a better antibacterial effect, but Ag has an active chemical property, is very easy to passivate on the surface when exposed to light, and is expensive, making it difficult to popularize.
[0004] Zr and Ti belong to the same group in the periodic table and have similar physical and chemical properties. However, zirconium has higher strength and wear resistance, and its corrosion resistance and biocompatibility (osteoblast growth) in simulated human body solutions are better than those of titanium. In addition, zirconium has a lower magnetic susceptibility (1.3×10 -6 cm 3 / g), elastic modulus (E Zr =68GPa) is closer to human bone, and the design of stable β-phase alloying can further reduce the elastic modulus. Therefore, the development of β-type zirconium-based alloys containing highly efficient antibacterial copper elements has antibacterial function and good mechanical compatibility (low elastic modulus) and magnetic compatibility (low magnetic susceptibility), which has broad application prospects in clinical implants (artificial joints, femoral head supports and dental implants, etc.) and MRI detection. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy in view of the deficiencies of the above-mentioned prior art. The β-type zirconium-based alloy effectively reduces the elastic modulus and magnetic susceptibility of the alloy by selecting Nb and Cu elements for alloying, while giving the alloy a long-lasting and efficient antibacterial property, solving the problem of MRI detection artifacts and postoperative bacterial infection caused by the high magnetic susceptibility of conventional implanted metal materials.
[0006] To solve the above technical problems, the technical solution adopted by the present invention is: an antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy, characterized in that it is composed of the following components in mass percentage: Nb 18% to 24%, Cu 4% to 10%, and the remainder is Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
[0007] First, the β-type Zr-Nb-Cu alloy of the present invention obtains a β-phase structure with a low modulus by adding a large amount of Nb. Since the elastic modulus of β-Zr (~60GPa, "~" here means approximately, the same below) is much lower than that of α-Zr (~100GPa), and it has more excellent comprehensive mechanical properties, the β-type Zr-Nb-Cu alloy of the present invention uses Nb as the main alloying element, and utilizes Nb to stabilize the β phase and infinitely dissolve with Zr to produce a strong solid solution strengthening effect, which effectively reduces the elastic modulus of the alloy while improving the strength, hardness, wear resistance and corrosion resistance of the alloy. During the research process of the present invention, it was found that when the mass percentage of Nb in the alloy is slightly higher than the eutectoid transformation point (~18%), the Zr-Nb binary alloy can obtain a fully stable β phase at room temperature; at the same time, the magnetic susceptibility of Nb (2.24×10 -6 cm 3 / g) is less than Ti, but still higher than Zr. Considering that excessive Nb content increases the magnetic susceptibility of the alloy and causes coarse organization and reduces mechanical properties. Therefore, the mass percentage of Nb in the β-type Zr-Nb-Cu alloy is controlled to be 18% to 24%.
[0008] Secondly, the present invention is the first to design Cu alloying based on β-type Zr-Nb alloy, further reducing the magnetic susceptibility of β-type Zr-Nb-Cu alloy and making the alloy have antibacterial function. During the research process of the present invention, it was found that when Zr forms an alloy with negative magnetic metal, the magnetic susceptibility of the alloy will be significantly reduced. At room temperature, Cu is a negative magnetic metal with a magnetic susceptibility of only -0.09×10 -6 cm 3 / g. Therefore, the present invention uses Cu element for alloying to effectively reduce the magnetic susceptibility of Zr-based alloys and reduce the artifact problem during MRI detection. More importantly, Cu is an essential trace element for the human body and has a strong antibacterial effect. Its addition will give the alloy significant antibacterial ability. At the same time, the Cu element in the alloy of the present invention is mainly in the form of solid solution and Zr 3 Cu exists in the form of Zr 3 The α-type alloy in which Cu exists in the form of α-type Zr-Nb alloy of the present invention has a higher sterilization rate. Since the mass percentage of solid solution Cu is greater than 3%, good antibacterial properties can be exhibited, and the addition of Cu element greater than 10% will cause brittle fracture of the alloy. Therefore, considering the mechanical properties and antibacterial effects, the mass percentage of Cu in the β-type Zr-Nb-Cu alloy of the present invention is controlled to be 4% to 10%.
[0009] The above-mentioned antibacterial magnetic compatible medical β-type Zr-Nb-Cu alloy is characterized by comprising the following components in mass percentage: Nb 22%, Cu 4% to 7%, and the balance is Zr and unavoidable impurity elements. The β-type Zr-Nb-Cu alloy of the preferred component has a lower elastic modulus (E=50.8GPa~59.1GPa) and magnetic susceptibility (χ g =1.16×10 -6 cm 3 / g~1.33×10 -6 cm 3 / g), which is more suitable for human bone and MRI detection; at the same time, the antibacterial rate of β-type Zr-Nb-Cu alloy increases with the increase of copper content, and the antibacterial rate against Staphylococcus aureus can reach 95.9% to 99.99%, with a strong antibacterial effect.
[0010] The above-mentioned antibacterial magnetic compatible medical β-type Zr-Nb-Cu alloy is characterized in that the elastic modulus of the β-type Zr-Nb-Cu alloy is 49.0GPa to 59.1GPa, the magnetic susceptibility is 1.16×10-6 cm 3 / g~1.33×10 -6 cm 3 / g, and the antibacterial rate against Staphylococcus aureus is greater than 95.9%.
[0011] The β-type Zr-Nb-Cu alloy of the present invention has a strong antibacterial effect, and the antibacterial rate against Staphylococcus aureus is greater than 95.9%, which can solve the problem of infection after implantation. Compared with the existing medical titanium alloy, the β-type Zr-Nb-Cu alloy has a lower elastic modulus (49.0GPa to 59.1GPa) and magnetic susceptibility (1.16×10 -6 cm 3 / g~1.33×10 -6 cm 3 / g), which is more suitable for human bone and nuclear magnetic resonance (MRI) detection; in addition, the antibacterial element Cu in the β-type Zr-Nb-Cu alloy is an essential trace element for the human body, has no cytotoxicity, and has low raw material cost, which avoids the excessive dependence of most medical alloys on precious metal elements and reduces the research and development and production costs of the alloy.
[0012] At the same time, the present invention also discloses a method for preparing the above Zr-Nb-Cu alloy, characterized in that the method comprises the following steps:
[0013] Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product β-type Zr-Nb-Cu alloy;
[0014] Step 2: Alloy smelting: The raw materials weighed in step 1 are placed in a water-cooled copper crucible, and evacuated and argon gas is introduced before smelting in a non-consumable vacuum arc furnace.
[0015] The raw materials used in the present invention are industrial-grade sponge zirconium, copper and niobium particles with a mass purity exceeding 99.0%, all of which can be purchased from the market; preferably, in order to avoid excessive content of impurity elements affecting the corrosion resistance and biocompatibility of the alloy, the sponge zirconium is nuclear grade, and the mass purity of the copper and niobium particles is above 99.9%.
[0016] The above method is characterized in that the order in which the raw materials are placed in the water-cooled copper crucible in step 2 is: copper particles, zirconium sponge, and niobium particles. The present invention uses a non-consumable vacuum arc furnace equipped with a water-cooled copper crucible to smelt the alloy. Considering that the melting point difference between copper (1083°C) and matrix zirconium (1852°C) is too large, low-melting-point copper particles are placed at the bottom of the crucible during smelting and zirconium sponge is spread on it. Finally, high-melting-point niobium particles are placed on the zirconium sponge to prevent the volatilization and loss of low-melting-point copper elements during smelting, thereby ensuring the accuracy of the composition of the β-type Zr-Nb-Cu alloy.
[0017] The above method is characterized in that the vacuum degree of the non-consumable vacuum arc furnace smelting in step 2 is 2×10 -3 Pa~5×10 -3 Pa, argon pressure is -50kPa~70kPa, smelting voltage is 220V, smelting current is controlled to be 420A~450A, maintained for 120s~180s, and smelting times are 6~7 times. The present invention puts the raw materials into a water-cooled copper crucible for vacuum treatment, passes argon gas for smelting, controls the smelting voltage to be 220V, controls the smelting current to be 420A~450A, maintained for 120s~180s, and then slowly adjusts the smelting current to 0A, so that the cooling time of the alloy from liquid solidification to solid is 15s~40s, and the alloy continues to be cooled in the water-cooled copper crucible after solidification, and the duration of the entire cooling process is 500s~800s; at the same time, considering that the density difference between the matrix zirconium and copper and niobium is too large, in order to ensure uniform composition and no segregation, the alloy is repeatedly smelted 6~7 times, and finally a β-type Zr-Nb-Cu alloy with uniform composition is obtained.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. Compared with the existing medical titanium alloys, the β-type Zr-Nb-Cu alloy of the present invention has a lower elastic modulus (49.0 GPa to 59.1 GPa) and magnetic susceptibility (1.16 × 10 -6 cm 3 / g~1.33×10 -6 cm 3 / g), which is more suitable for human bone and magnetic resonance imaging (MRI) detection.
[0020] 2. The β-type Zr-Nb-Cu alloy of the present invention uses Nb as the main alloying element to ensure the acquisition of a stable β phase structure, which is infinitely miscible with Zr to produce a strong solid solution strengthening effect, effectively reducing the elastic modulus of the alloy while improving the strength, hardness, wear resistance and corrosion resistance of the alloy.
[0021] 3. The β-type Zr-Nb-Cu alloy of the present invention is in full β phase at room temperature, which can dissolve more Cu elements and is different from conventional Zr-only alloys. 3 Compared with the α-type zirconium alloy with Cu phase, the Cu element in this alloy is mainly in the solid solution state and Zr 3 The simultaneous presence of Cu phases ensures long-lasting and highly effective antibacterial properties, with an antibacterial rate of up to 99.99%, which can solve the problem of bacterial infection caused by clinical implantation.
[0022] 4. The alloying elements Nb and Cu used in the β-type Zr-Nb-Cu alloy of the present invention are non-cytotoxic and have good biocompatibility. In particular, the Cu element is also an essential trace element for the human body, and the raw material cost is low, which effectively avoids the excessive dependence on precious metal elements (Ta, Ag) in existing medical alloys and reduces the research and development and production costs of the alloy.
[0023] 5. The β-type Zr-Nb-Cu alloy of the present invention can be used as a clinical implant material to significantly reduce the impact of postoperative bacterial infection and MRI detection artifacts, better meet the needs of the development of metal-based biomedical materials, and provide medical workers with more choices of implant materials.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of the β-type Zr—Nb—Cu alloys prepared in Examples 1 to 5 of the present invention and the β-type Zr—Nb alloy prepared in Comparative Example 1.
[0026] Figure 2 The engineering stress-strain curves of the β-type Zr-Nb-Cu alloys prepared in Examples 1 to 5 of the present invention.
[0027] Figure 3 This is a graph showing the magnetic susceptibility results of the β-type Zr—Nb—Cu alloys prepared in Examples 1 to 5 of the present invention and the β-type Zr—Nb alloy prepared in Comparative Example 1.
[0028] Figure 4 The coating result diagram of the β-Zr-Nb-Cu alloy prepared in Examples 1 to 5 of the present invention and the β-Zr-Nb alloy prepared in Comparative Example 1 after culturing Staphylococcus aureus for 24 hours. DETAILED DESCRIPTION
[0029] Example 1
[0030] The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment is composed of the following components in mass percentage: Nb 22%, Cu 4%, and the balance Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
[0031] The preparation method of the antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment comprises the following steps:
[0032] Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product Zr-Nb-Cu alloy;
[0033] Step 2: Alloy smelting: Place the raw materials weighed in step 1 into a water-cooled copper crucible in the order of copper particles, zirconium sponge, and niobium particles, and evacuate to a vacuum degree of 5×10 -3 Pa, argon gas was introduced to a pressure of -50 kPa for non-consumable vacuum arc furnace melting, the melting voltage was controlled to 220 V, the melting current was 420 A, and the melting current was maintained for 150 s. Then the melting current was slowly adjusted to 0 A. After the alloy solidified from liquid to solid, it was continued to be cooled in a water-cooled copper crucible. The whole cooling process lasted for 600 s. The alloy was repeatedly melted 7 times to obtain β-type Zr-Nb-Cu alloy.
[0034] Example 2
[0035] The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment is composed of the following components in mass percentage: Nb 22%, Cu 7%, and the balance Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
[0036] The preparation method of the antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment comprises the following steps:
[0037] Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product Zr-Nb-Cu alloy;
[0038] Step 2: Alloy smelting: Place the raw materials weighed in step 1 into a water-cooled copper crucible in the order of copper particles, zirconium sponge, and niobium particles, and evacuate to a vacuum degree of 5×10 -3 Pa, argon gas was introduced to a pressure of -50 kPa for non-consumable vacuum arc furnace melting, the melting voltage was controlled to 220 V, the melting current was 450 A, and the melting current was maintained for 150 s. Then the melting current was slowly adjusted to 0 A. After the alloy solidified from liquid to solid, it was continued to be cooled in a water-cooled copper crucible. The whole cooling process lasted for 600 s. The alloy was repeatedly melted 7 times to obtain β-type Zr-Nb-Cu alloy.
[0039] Example 3
[0040] The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment is composed of the following components in mass percentage: Nb 22%, Cu 10%, and the balance Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
[0041] The preparation method of the antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment comprises the following steps:
[0042] Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product Zr-Nb-Cu alloy;
[0043] Step 2: Alloy smelting: Place the raw materials weighed in step 1 into a water-cooled copper crucible in the order of copper particles, zirconium sponge, and niobium particles, and evacuate to a vacuum degree of 5×10 -3 Pa, argon gas was introduced to a pressure of -70 kPa for non-consumable vacuum arc furnace melting, the melting voltage was controlled to 220 V, the melting current was 450 A, and the melting current was maintained for 180 s. Then the melting current was slowly adjusted to 0 A. After the alloy solidified from liquid to solid, it was continued to be cooled in a water-cooled copper crucible. The whole cooling process lasted for 600 s. The alloy was repeatedly melted 7 times to obtain β-type Zr-Nb-Cu alloy.
[0044] Example 4
[0045] The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment is composed of the following components in mass percentage: Nb 18%, Cu 4%, and the balance Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
[0046] The preparation method of the antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment comprises the following steps:
[0047] Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product Zr-Nb-Cu alloy;
[0048] Step 2: Alloy smelting: Place the raw materials weighed in step 1 into a water-cooled copper crucible in the order of copper particles, zirconium sponge, and niobium particles, and evacuate to a vacuum degree of 2×10 -3 Pa, argon gas is introduced to a pressure of -50 kPa for non-consumable vacuum arc furnace melting, the melting voltage is controlled to 220 V, the melting current is 450 A, and the melting current is maintained for 180 s, and then the melting current is slowly adjusted to 0 A. After the alloy solidifies from liquid to solid, it is continued to be cooled in a water-cooled copper crucible. The whole cooling process lasts for 600 s. The alloy is repeatedly melted 6 times to obtain β-type Zr-Nb-Cu alloy.
[0049] Example 5
[0050] The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment is composed of the following components in mass percentage: Nb 24%, Cu 4%, and the balance Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
[0051] The preparation method of the antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy of this embodiment comprises the following steps:
[0052] Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product Zr-Nb-Cu alloy;
[0053] Step 2: Alloy smelting: Place the raw materials weighed in step 1 into a water-cooled copper crucible in the order of copper particles, zirconium sponge, and niobium particles, and evacuate to a vacuum degree of 2×10 -3 Pa, argon gas was introduced to a pressure of -50 kPa for non-consumable vacuum arc furnace melting, the melting voltage was controlled to 220 V, the melting current was 450 A, and the melting current was maintained for 150 s. Then the melting current was slowly adjusted to 0 A. After the alloy solidified from liquid to solid, it was continued to be cooled in a water-cooled copper crucible. The whole cooling process lasted for 600 s. The alloy was repeatedly melted 7 times to obtain β-type Zr-Nb-Cu alloy.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that this comparative example is a β-type Zr-Nb alloy, which is composed of the following components in mass percentage: Nb 22%, and the balance Zr and unavoidable impurity elements.
[0056] Performance Testing
[0057] (1) The phase compositions of the β-Zr-Nb-Cu alloys prepared in Examples 1 to 5 of the present invention and the β-Zr-Nb alloy prepared in Comparative Example 1 were analyzed by X-ray diffractometer. The corresponding X-ray diffraction patterns are shown in FIG. Figure 1 .from Figure 1 It can be seen that the Zr-Nb-Cu alloy matrix prepared in Examples 1 to 5 is β phase, with a small amount of Zr 3 Cu phase, while the Zr-Nb alloy phase composition in Comparative Example 1 is a single β phase; with the increase of Cu content, Zr in the β-type Zr-Nb-Cu alloy of the present invention 3 The volume fraction of the Cu phase increases from ~2% (Example 1) to ~5% (Example 2) and ~8% (Example 3)
[0058] (2) The tensile mechanical properties of the β-Zr-Nb-Cu alloys prepared in Examples 1 to 5 of the present invention and the β-Zr-Nb alloy prepared in Comparative Example 1 were tested. The specific process is as follows: the alloy ingots were cut into dog-bone tensile specimens with a gauge length of 12.5 mm, a thickness of 1.8 mm, and a width of 4 mm by a wire cutting machine, and then the tensile mechanical properties were tested on a UTM5105X universal testing machine. The results are shown in FIG. Figure 2 and Table 1.
[0059] (3) The magnetic susceptibility (χ) of the β-Zr-Nb-Cu alloys prepared in Examples 1 to 5 of the present invention and the β-Zr-Nb alloy prepared in Comparative Example 1 was tested. The specific process was as follows: the alloy ingots were cut into 3 mm × 3 mm × 3 mm square samples by a wire cutting machine, the surface oxide scale was polished clean with metallographic sandpaper, and then the magnetic susceptibility was tested in a VSM vibrating magnetometer (magnetic field strength: 2 T). The results are shown in Table 1. Figure 3 and Table 1.
[0060] (4) According to QB / T 2591-2003 "Test Method and Antibacterial Effect of Antibacterial Plastics", the antibacterial properties of the β-Zr-Nb-Cu alloys prepared in Examples 1 to 5 of the present invention and the β-Zr-Nb alloy prepared in Comparative Example 1 were tested by direct contact test. The specific process is: the alloy ingots were cut into φ15 mm×2 mm disc samples by a wire cutting machine, and the disc samples were subjected to antibacterial experiments and antibacterial evaluation by a coating method and a plate counting method. When the antibacterial rate was greater than 90%, it was determined to have antibacterial properties, and when the antibacterial rate was greater than 99%, it was determined to have strong antibacterial properties. The results are shown in Table 1. Figure 4 and Table 1.
[0061] Table 1
[0062]
[0063] Combining Table 1 and Figures 2 to 4 It can be seen that compared with the lower elastic modulus, higher magnetic susceptibility and lower antibacterial rate of the β-type Zr-Nb alloy in Comparative Example 1, the β-type Zr-Nb-Cu alloy prepared in Examples 1 to 5 of the present invention has excellent strength performance, and the elastic modulus is 49.0 GPa to 59.1 GPa, the magnetic susceptibility is 1.16×10 -6 cm 3 / g~1.33×10 -6 cm 3 / g, and the antibacterial rate against Staphylococcus aureus within 24 hours is greater than 95.9%, that is, it has a lower elastic modulus and magnetic susceptibility, as well as long-lasting and efficient antibacterial properties, and is more suitable for human bone and nuclear magnetic resonance (MRI) detection.
[0064] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy, characterized in that: The invention is composed of the following components in percentage by mass: Nb 18% to 24%, Cu 4% to 10%, and the balance Zr and inevitable impurity elements; the inevitable impurity elements include Fe, Al, Hf, Si, Ta and Ni.
2. The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy according to claim 1, characterized in that: The invention comprises the following components in percentage by mass: Nb 22%, Cu 4% to 7%, and the balance Zr and inevitable impurity elements.
3. The antibacterial magnetically compatible medical β-type Zr-Nb-Cu alloy according to claim 1 or 2, characterized in that: The elastic modulus of the β-type Zr-Nb-Cu alloy is 49.0 GPa to 59.1 GPa, and the magnetic susceptibility is 1.16×10 -6 cm 3 / g~1.33×10 - 6 cm 3 / g, and the antibacterial rate against Staphylococcus aureus is greater than 95.9%.
4. A method for preparing the Zr-Nb-Cu alloy according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1, weighing raw materials: weighing raw material sponge zirconium, copper and niobium particles with a mass purity of more than 99.0% respectively according to the composition of the target product β-type Zr-Nb-Cu alloy; Step 2: Alloy smelting: The raw materials weighed in step 1 are placed in a water-cooled copper crucible, and evacuated and argon gas is introduced before smelting in a non-consumable vacuum arc furnace.
5. The method according to claim 4, characterized in that The order in which the raw materials are placed in the water-cooled copper crucible in step 2 is: copper particles, zirconium sponge, and niobium particles.
6. The method according to claim 4, characterized in that The vacuum degree of the non-consumable vacuum arc furnace melting in step 2 is 2×10 -3 Pa~5×10 -3 Pa, argon pressure is -50kPa~70kPa, melting voltage is 220V, melting current is 420A~450A, melting time is 120s~180s, and melting times is 6~7 times.
Citation Information
Patent Citations
Low-magnetic-susceptibility beta-type Zr-Nb-Ta series alloy and preparation method thereof
CN108149071A
Omega-rich medical zirconium-based alloy and preparation method thereof
CN114277283A
Magnetically compatible Zr-Nb-Cu biomedical alloy with low elastic modulus as well as preparation method and application of magnetically compatible Zr-Nb-Cu biomedical alloy
CN117947316A
Magnetically compatible beta-type biomedical zirconium alloy as well as preparation method and application thereof
CN117965957A
Cited By
Biomedical zirconium alloy with ultralow elastic modulus and preparation method thereof
CN120796777A